OXIDATIVE STRESS, SIALIC ACID AND TOTAL ANTIOXIDANT STATUS IN PATIENTS WITH TYPE2 DIABETES MELLITUS - V.C.RENJU; K.SANTHA; S.SETHUPATHY (International Journal of Pharma and Bio Sciences, 2012)
Oxidative stress plays a major role in the pathogenesis of diabetic mellitus. The present study was undertaken to assess lipid peroxidation by TBARS, antioxidant status using FRAP and inflammatory status using sialic acid in patients with Type2 Diabetes mellitus and healthy individuals in rural population. AnthropometricBiochemical, Fasting insulin, HOMA-IR were estimated in both groups. We observed a positive correlation among FBS,TBARS and Sialic acid and they are negatively correlated with FRAP. In this study, we observed that increased blood glucose may play a role in the pathogenesis of oxidative stress which could have lead to reduction of the total antioxidant power.